Holocene landscape evolution and its interaction with human activities in the southern piedmont of Taihang Mountain, Central China - Zhang, Xiaohu; Yang, Shugang; Lu, Peng; Li, Yaping; Chen, Panpan; Xia, Zhengkai (Frontiers in Plant Science, 2022)
Piedmont zones have been the areas of high human activity since ancient times. However, the environmental mechanism for early humans exploiting piedmont zones is still unclear. Here we present a case study about early human-environment interaction in the piedmont of Taihang Mountain, with prominent ecological and cultural significance in Chinese history. Using dating and pollen analysis, we reconstruct the regional landscape evolution in the Fengtougang (FTG) site of southern Taihang Mountain during the Holocene. The results show that the area has been dominated by terrestrial plants since the late Longshan culture (4000 BP), including a large number of pinus, artemisia, spiraea, and gramineae and a few cattail and other aquatic herbs. During early history (4000-2000 BP), there is a combination of pinus, artemisia, spiraea, compositae, and selaginella chinensis, with a few aquatic plants. Since the late history (500 BP), Chinese selaginella, pinus, selaginella, and sedge families dominate, with no aquatic plant pollen found. Combining the detailed geoarchaeological survey, grain size analysis, and magnetic susceptibility investigation, we argue that there should be a landscape transition from extensive floodplain during the early-middle Holocene (10000-4000 BP) to sparse forest grassland and river-lake interlacing distribution during the late Longshan culture in the region. With river downcutting and watercourse fixation, the massively shrunk flooded area provides a suitable habitat for human settlement since the late Longshan culture. From then on, human activities begin to move to the study region on a large scale, followed by continuous cultural development and brilliant early civilization.